Anodal Transcranial Direct Current Stimulation Could Modulate Cortical Excitability and the Central Cholinergic System in Akinetic Rigid-Type Parkinson's Disease: Pilot Study - Oh, Eungseok; Park, Jinse; Youn, Jinyoung; Jang, Wooyoung (Frontiers in Neurology, 2022)
Background: Transcranial direct current stimulation (tDCS) is a noninvasive technique that has been widely studied as an alternative treatment for Parkinson’s disease (PD). However, its clinical benefit remains unclear. In this study, we aimed to investigate the effect of tDCS on the central cholinergic system and cortical excitability in mainly akinetic rigid-type PD patients. Methods: Eighteen PD patients were prospectively enrolled and underwent 5 sessions of anodal tDCS on the M1 area, which is on the contralateral side of the dominant hand. We excluded PD patients who had evident resting tremor of the hand to reduce the artifact of electrophysiologic findings. We compared clinical scales reflecting motor, cognitive, and mood symptoms between pre- and posttDCS. Additionally, we investigated the changes in electrophysiologic parameters, including short latency afferent inhibition (SAI) (%), which reflects the central cholinergic system. Results: The UPDRS-III, MoCA-K, and BDI scores were significantly improved after anodal tDCS (p < 0.01, p < 0.01, p < 0.01). Moreover, MEPAR (%) and integrated SAI showed significant improvement after tDCS (p < 0.01, p < 0.01). The mean values of the change in integrated SAI (%) were significantly correlated with the changes in UPDRS-III scores; however, the MoCA-K and BDI scores did not show differences. Conclusions: Anodal tDCS could influence the central cholinergic system, including frontal cortical excitability and depression in PD. This mechanism could underlie the clinical benefit of tDCS in PD patients.